A Comparative Study on the Theoretical Development of Functions of Language with Reference to Bühler, Jakobson, and Halliday (Universitas Islam Negeri Sunan Ampel Surabaya, 2021)
This paper attempts to describe and compare the functionalist explanations of the language of Bühler, Jakobson, and Halliday. These three functionalists are not the leading figures to propose the theory of functions of language, but their descriptions of the theoretical framework and the natural selection of language usages have proven to be more credible and therefore accepted by the linguistics community today. Since these functional insights are original conceptions, there have been significant theoretical developments, and there is now a large evidence base to authenticate the contemporary theoretical development. This study, thus, discusses the specific claims of the theoretical framework of the three functionalists, highlights their similarities, and differentiates major characteristics on the queries of how the functionalists explain their observations of functions of language and theory of language explain the multiplicity of language functions. This comparison has revealed that the functionalists initially have perceived the importance of an individual’s language as a social need and the ubiquity of these comparisons. The complexity of social comparisons presents a potentially fruitful explanation. Further, this paper recommends that explanations be considered for studying languages and other semiotic resources.